Perspectives on Scedosporium species and Lomentospora prolificans in lung transplantation: Results of an international practice survey from ESCMID fungal infection study group and study group for infections in compromised hosts, and European Confederation of Medical Mycology. Issue 5 (22nd July 2019) - Rammaert, Blandine; Puyade, Mathieu; Cornely, Oliver A.; Seidel, Danila; Grossi, Paolo; Husain, Shahid; Picard, Clément; Lass‐Flörl, Cornelia; Manuel, Oriol; Le Pavec, Jérôme; Lortholary, Olivier; ,
Abstract: Background: Scedosporium species and Lomentospora prolificans (S/L) are the second most common causes of invasive mold infections following Aspergillus in lung transplant recipients. Methods: We assessed the current practices on management of S/L colonization/infection of the lower respiratory tract before and after lung transplantation in a large number of lung transplant centers through an international practice survey from October 2016 to March 2017. Results: A total of 51 respondents from 45 lung transplant centers (17 countries, 4 continents) answered the survey (response rate 58%). S/L colonization was estimated to be detected in candidates by 48% of centers. Only 18% of the centers used a specific medium to detect S/L colonization. Scedosporium spp. colonization was a contraindication to transplantation in 10% of centers whereas L prolificans was a contraindication in 31%; 22% of centers declared having had 1‐5 recipients infected with S/L in the past 5 years. Conclusions: This survey gives an overview of the current practices regarding S/L colonization and infection in lung transplant centers worldwide and underscores the need of S/L culture procedure standardization before implementing prospective studies.